Human serum albumin or polyvinyl alcohol can only partially replace human plasma during in vitro red cell production from PBMC - Marie-José A. G. Claessen; Nurcan Yagci; Gerard van Mierlo; Marie José Kersten; Marieke von Lindern; Emile van den Akker (Scientific Reports)
Abstract Transfusion of donor-derived red blood cells (RBC) depends on donor availability. Alloimmunization can limit the availability of transfusion units, particularly for chronically transfused patients. In vitro cultured, customizable RBC (cRBC) would negate these concerns and provide infinite RBC products. Previously, we developed a defined medium based on good manufacturing practice (GMP) requirements. To optimize medium conditions with regards to reproducibility and cost effectiveness, we tested the requirement for plasma during the differentiation phase and the replacement of HSA by polyvinyl alcohol (PVA) during the expansion and differentiation phase. We show that 5% plasma is essential to enhance cell count, enucleation% and mostly stability of cRBC during the differentiation phase. During the expansion phase HSA could be replaced by PVA without compromising the expansion capacity. Substitution of HSA by PVA even increased the number of cells at the end of the expansion phase. During the differentiation phase PVA could also replace HSA, but only in the presence of plasma. Plasma is still essential to achieve an optimum yield of enucleated cRBC, likely by stabilizing enucleated cRBC. Substitution of HSA by PVA is a new advancement in the development of a, defined, cost-effective culture medium to culture cRBC for all.